The Impacts of Changing Patterns in Traditional Chena Cultivation in Sri Lanka: A Study with Reference to the Monaragala District - Dissanayake, D.M. Karunadasa (My University, 2012)
The Sri Lankan economy has been constructed around 'agriculture' for a long period. Agriculture can be divided into two sections: Subsistence and Plantation (commercial) agriculture. The subsistence agricultural sector can again be divided into two sections as “Chena cultivation” and “Paddy cultivation”. There is evidence to prove that the livelihood of the ancient people of Sri Lanka was formed by chena cultivation, which is mainly done in the Maha season. Chena cultivation is based on shifting from place to place and using primary methods of cultivation which do not use water supply methods and chemical fertilizer like in wet paddy cultivation. In the past, chena farmers had cultivated various crops in the chena for food requirements of their families. After that chena farmers have cultivated several crops especially for the market, as well as to meet their family requirements. In the recent three decades chena farmers had tried to change the chena cultivation to become a profitable enterprise given the market oriented economy. To meet these objectives the farmers had given more attention to use of new technical methodology to increase the yield of the chena. As a result, present chena cultivation in Sri Lanka has shown vast differences compared to traditional chena cultivation. Most of the farmers use machines to cut the forest. Tractors are used for land preparation. Imported seeds and chemical fertilizers are also used. After preparation of the land they cultivate only one or two crops such as Maize and Ground nuts as commercial crops. In addition paddy is also cultivated in the chena.